2018
DOI: 10.1002/mcf2.10002
|View full text |Cite
|
Sign up to set email alerts
|

Assisting Ecosystem‐Based Fisheries Management Efforts Using a Comprehensive Survey Database, a Large Environmental Database, and Generalized Additive Models

Abstract: Statistical habitat models, such as generalized additive models (GAMs), are key tools for assisting ecosystembased fisheries management (EBFM) efforts. Predictions from GAMs can be used, for example, to produce preference functions for the ecosystem-modeling platform Ecospace; preference functions permit a flexible representation of spatial distribution patterns in Ecospace by defining the preferences of marine organisms for certain environmental parameter values. Generalized additive model predictions can als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 86 publications
1
48
0
Order By: Relevance
“…Based on previous research (e.g. Austin, ; Grüss, Chagaris, et al, ; Leathwick, Elith, & Hastie, ), for each life stage of each species of interest, one should ideally consider: (a) only monitoring programs providing at least 20–50 encounter estimates; and (b) only years associated with at least four encounter estimates.…”
Section: Methodsmentioning
confidence: 99%
“…Based on previous research (e.g. Austin, ; Grüss, Chagaris, et al, ; Leathwick, Elith, & Hastie, ), for each life stage of each species of interest, one should ideally consider: (a) only monitoring programs providing at least 20–50 encounter estimates; and (b) only years associated with at least four encounter estimates.…”
Section: Methodsmentioning
confidence: 99%
“…Eastings and northings were measured based on the distance from a reference location to each sampling site. If a pair of variables exhibited a correlation coefficient value higher than 0.7, the variable that displayed a lower correlation with the other variables was retained for the following analyses (Guisan et al 2002;Leathwick et al 2006;Grüss et al 2018). Among the 13 sampling sites, sites 3, 4, 6, 7, 9, 10, 11, and 12 were inside of the experimental zone of the marine protected area and sites 1, 2, 5, 8, and 13 were outside of the marine protected area.…”
Section: Methodsmentioning
confidence: 99%
“…We did not choose this option, because GAMMs are computationally intensive and are likely to face convergence issues when fitted to very large monitoring datasets like ours. However, Grüss et al (2017a) showed that the spatial patterns of probability of encounter predicted by GAMs treating monitoring program as a fixed effect factor are unaffected by the monitoring program factor, and that the gross magnitude of the probabilities of encounter predicted by these GAMs are only slightly affected by the monitoring program factor. We employed thin-plate regression splines with shrinkage, and each thin-plate regression spline was limited to four degrees of freedom (Roberts et al, 2016;Mannocci et al, 2017).…”
Section: Surface Salinity Unitless Terrain Ruggedness Index Unitlessmentioning
confidence: 96%
“…. , x n are the environmental covariates selected after the collinearity analysis; and year and monitoring program are "nuisance variables" (i.e., variables that are not of immediate interest but that must be accounted for in the analysis) treated as fixed effect factors (Farmer and Karnauskas, 2013;Grüss et al, 2016aGrüss et al, , 2017a. The fact that year and monitoring program are fixed effect factors entails that it will be necessary to choose a given year and a given monitoring program to make predictions with fitted GAMs (in this case, the average year effect and the monitoring program effect with the highest selectivity; Punt et al, 2000;Maunder and Punt, 2004;Farmer and Karnauskas, 2013;Grüss et al, 2016a; see subsection Production of Distribution Maps for the GOM LME from the Predictions Made by Fitted Binomial GAMs).…”
Section: Surface Salinity Unitless Terrain Ruggedness Index Unitlessmentioning
confidence: 99%
See 1 more Smart Citation